Impact of ERG3 mutations and expression of ergosterol genes controlled by UPC2 and NDT80 in Candida parapsilosis azole resistance. (August 2017) - Branco, J.; Ola, M.; Silva, R.M.; Fonseca, E.; Gomes, N.C.; Martins-Cruz, C.; Silva, A.P.; Silva-Dias, A.; Pina-Vaz, C.; Erraught, C.; Brennan, L.; Rodrigues, A.G.; et al.
Abstract: Objectives: Candida parapsilosis is a healthcare-related fungal pathogen particularly common among immunocompromised patients. Our understanding of antifungal resistance mechanisms in C. parapsilosis remains very limited. We previously described an azole-resistant strain of C. parapsilosis (BC014RPSC ), obtained following exposure in vitro to posaconazole. Resistance was associated with overexpression of ergosterol biosynthetic genes ( ERG genes), together with the transcription factors UPC2 ( CPAR2-207280 ) and NDT80 ( CPAR2-213640 ). The aim of this study was to identify the mechanisms underlying posaconazole resistance of the BC014RPSC strain. Methods: To identify the causative mutation, we sequenced the genomes of the susceptible (BC014S) and resistant (BC014RPSC ) isolates, using Illumina technology. Ergosterol content was assessed in both strains by mass spectrometry. UPC2 and NDT80 genes were deleted in BC014RPSC strain. Mutants were characterized regarding their azole susceptibility profile and ERG gene expression. Results: One homozygous missense mutation (R135I) was found in ERG3 ( CPAR2-105550 ) in the azole-resistant isolate. We show that Erg3 activity is completely impaired, resulting in a build up of sterol intermediates and a failure to generate ergosterol. Deleting UPC2 and NDT80 in BC014RPSC reduces the expression of ERG genes and restores susceptibility to azole drugs. Conclusions: A missense mutation in the ERG3 gene results in azole resistance and up-regulation of ERG genes expression. We propose that this mutation prevents the formation of toxic intermediates when cells are treated with azoles. Resistance can be reversed by deleting Upc2 and Ndt80 transcription factors. UPC2 plays a stronger role in C. parapsilosis azole resistance than does NDT80 .